Ventricular Fibrillation with Brugada Syndrome: A Case Report - Nabi, Shaila; Tushar, Asif Zaman; Ferdaushi, Umme Habiba; Islam, Mainul; Uddin, Farhad; Ali, M Atahar (Cardiovascular Journal, 2015)
Brugada syndrome is a potentially lethal and eminently treatable entity that may present with palpitations or syncope. This article presents the case of a young patient with Brugada syndrome and reviews key features in the epidemiology, pathophysiology, diagnosis, treatment and prognosis of this condition. Cardiovasc. j. 2015; 8(1): 69-72